2018
DOI: 10.1039/c8gc00434j
|View full text |Cite
|
Sign up to set email alerts
|

Modular biomanufacturing for a sustainable production of terpenoid-based insect deterrents

Abstract: A sustainable production process of a new terpenoid-based insect deterrent which might serve as a future alternative to synthetic solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 81 publications
0
40
0
Order By: Relevance
“…The cembrene-type diterpenes display diverse bioactivities, including cytotoxic, insect deterrent and antimicrobial. Relevant work on insecticidal cembrenes has recently been reported 43 . Similarly, the single mutation of W288G alters to product to (1 R ,3 E ,7 E ,11 S ,12 S )−3,7,18-dolabellatriene.…”
Section: Discussionmentioning
confidence: 99%
“…The cembrene-type diterpenes display diverse bioactivities, including cytotoxic, insect deterrent and antimicrobial. Relevant work on insecticidal cembrenes has recently been reported 43 . Similarly, the single mutation of W288G alters to product to (1 R ,3 E ,7 E ,11 S ,12 S )−3,7,18-dolabellatriene.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the external loop of the ERC allowed the semi-continuous product recovery, reaching (+)-zizaene titers of 93.4 mg L −1 . Such improvements have also been obtained by the use of ERC in other terpenes studies, such as monoterpene carvone (225 mg L −1 ) [37] and diterpene cembratriene-ol (78.9 mg L −1 ) [50].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, overexpression of cembratrien-ol synthase gene using either trichome-specific CYP450 or Cauliflower mosaic virus 35S promoters greatly increased aphid resistance by promoting the accumulation of CBT-diols in tobacco plants [23]. Recent studies show that the recombinant Escherichia coli can be used to generate 78.9 ± 2.4 mg·L −1 CBT-ol in a 50 L bioreactor, and in vivo and in vitro bioactivity studies confirmed the insecticidal characteristics [24]. Therefore, tobacco cembranoid diterpenes can be researched for the development of insecticides due to their insecticidal activity [22,23,24].…”
Section: Bioactivities Of Tobacco Cembranoid Diterpenesmentioning
confidence: 99%
“…Recent studies show that the recombinant Escherichia coli can be used to generate 78.9 ± 2.4 mg·L −1 CBT-ol in a 50 L bioreactor, and in vivo and in vitro bioactivity studies confirmed the insecticidal characteristics [24]. Therefore, tobacco cembranoid diterpenes can be researched for the development of insecticides due to their insecticidal activity [22,23,24].…”
Section: Bioactivities Of Tobacco Cembranoid Diterpenesmentioning
confidence: 99%